ESBL/pAmpC-producing Enterobacterales in common leopard geckos (Eublepharis macularius) and central bearded dragons (Pogona vitticeps) from Portugal - Valença, Andreia; Fernandes, Gonçalo; Smolders, Joaquim; Patrício, Rui; Belas, Adriana (Frontiers in Veterinary Science, 2025)
Common leopard geckos (Eublepharis macularius) and central bearded dragon (Pogona vitticeps) are widely kept as pets but can harbor pathogenic bacteria, including antimicrobial-resistant (AMR) bacteria. This study aimed to research the frequency of β-lactamase-producing Enterobacterales in these two reptile species. A total of 132 samples were collected from the oral and cloacal cavities of healthy common leopard geckos and central bearded dragons in the Lisbon area, Portugal. Antimicrobial resistance was assessed for third-generation cephalosporin (3GC)-resistant Enterobacterales. The results revealed that 3GC-resistant Enterobacterales were observed in 17.9% (n = 14/78) of the reptiles. The most commonly identified species were: Citrobacter freundii and Klebsiella aerogenes. Furthermore, some isolates produced extended-spectrum β-lactamases (ESBLs) and AmpC β-lactamases (AmpC) encoding genes such as blaCMY-2, blaCTX-M-15, and blaTEM-1. These findings emphasize the potential role of these reptiles in the spread of AMR bacteria, particularly in urban settings where human- animal interactions are frequent. Given the zoonotic risks, this study emphasizes the importance of continued surveillance and responsible antimicrobial use in both veterinary and human medicine to mitigate the spread of AMR bacteria.